2021
DOI: 10.1136/bmjopen-2020-043863
|View full text |Cite
|
Sign up to set email alerts
|

Impact of temperature and relative humidity on the transmission of COVID-19: a modelling study in China and the United States

Abstract: ObjectivesWe aim to assess the impact of temperature and relative humidity on the transmission of COVID-19 across communities after accounting for community-level factors such as demographics, socioeconomic status and human mobility status.DesignA retrospective cross-sectional regression analysis via the Fama-MacBeth procedure is adopted.SettingWe use the data for COVID-19 daily symptom-onset cases for 100 Chinese cities and COVID-19 daily confirmed cases for 1005 US counties.ParticipantsA total of 69 498 case… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
110
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(124 citation statements)
references
References 42 publications
11
110
0
3
Order By: Relevance
“…18). This is despite theoretical demonstrations of the potential role of environment in driving future seasonality of SARS-CoV-2 (22,32) and the empirical evidence in structurally similar viruses outlined above. Efforts to incorporate climate into COVID-19 forecasting have focused on regression-type models of cases and fatalities (e.g., ref.…”
Section: Significancementioning
confidence: 93%
“…18). This is despite theoretical demonstrations of the potential role of environment in driving future seasonality of SARS-CoV-2 (22,32) and the empirical evidence in structurally similar viruses outlined above. Efforts to incorporate climate into COVID-19 forecasting have focused on regression-type models of cases and fatalities (e.g., ref.…”
Section: Significancementioning
confidence: 93%
“…However, given the large number of undocumented SARS-CoV-2 infections 18 , the variations in the lag between infection and symptom onset, and the inconsistent lag between testing and reporting, using daily new confirmed cases may not be optimal for examining meteorological effects 19 . As a result, a few studies have used the reproduction number to estimate SARS-CoV-2 transmissibility 20 22 . One study reported high daily air temperature and high daily relative humidity (RH, the amount of water vapor in the air expressed as a percentage of the amount needed for saturation at a given temperature) to be associated with a reduced daily effective reproduction number ( R e , the mean number of new infections caused by a single infected person in a population in which some individuals may no longer be susceptible due to acquired immunity 23 ) for SARS-CoV-2 in both China and the U.S. 20 .…”
Section: Introductionmentioning
confidence: 99%
“…These regions had similar weather conditions during this period. Studies by many authors (Scafetta 2020;Tzampoglou and Loukidis 2020;Spena et al 2020;Haque and Rahman 2020;Wang et al 2021;Tobías and Molina 2020) confirm the negative impact of high temperature and high humidity on the number of infections and pandemic deaths. They suggest that the pandemic is likely to evolve in line with the seasonal temperature cycle.…”
Section: Empirical Research and Discussionmentioning
confidence: 94%